The challenges, potentials, and experts’ opinions on developing a Malaysian garden identity - Mohd Tahir, Osman; Kaboudarahangi, Mina (Universiti Putra Malaysia Press, 2014)
As well as generally being considered as symbols of national and country identity, gardens fulfill various functions within society such as being aesthetically beautiful, satisfying human needs, and also functioning as places for various activities. In accordance with this, the Malaysian government in her newly launched National Landscape Policy put forth a vision to achieve “The Most Beautiful Garden Nation” by the year 2020, reflecting a desire to develop a distinctive landscape identity for the country. Due to this, the National Landscape Department of Malaysia suggested developing a garden identity as an indispensable part of this vision because even though the country has great potential in the development of parks and gardens, an exclusive garden identity is still lacking. This paper aims to justify that the development of a garden identity could enhance national and landscape identities for the country. It is also presumed that such development faces several challenges. Moreover, the study intends to highlight Malaysia’s great potential for developing its gardens. A review of existing literature along with Malaysia’s new landscape policy was thus undertaken, and findings were then triangulated by conducting face-to-face interviews with Malaysian local landscape architects. Consequently, the importance of creating a unique garden identity corresponding with Malaysia’s new landscape policy was confirmed. Furthermore, challenges (which mainly relate to political, social, cultural, and economic viewpoints) and potentials for such development were recognised. The results can ultimately be utilised to contribute to the formation of gardens with distinct Malaysian identities.